Folklore through new media / Siti Zubaidah Raja Mhd Shahnuddin - Raja Mhd Shahnuddin, Siti Zubaidah (2017)
Folklore refers to the traditional beliefs and stories of a community. There are various kinds of folklore that includes folktales, myths, legends, beliefs, and practices (Emrich, 1946; Sims & Stephens, 2005). However, through the turn of wheel, in this twenty first century, the generation's tendency is more to be engulfed in technology. Folklore in this era is experiencing the change from the traditional to the modern approach of new media. John Saunders (2011) claims, children today are very different from children centuries ago. At a very young age, children now are being encultured with media literacy. Due to this, the concept by Marshall McLuhan (19111980) that the medium is the message is applied in this research in attempts to identified intermediary medium that is most suitable to the children nowadays and through it, we can elaborate the effects left behind by the medium towards this old tradition of folklore.